Curriculum and pedagogical developments within university surveying & geomatics courses - Young, Garfield Osbourne (2013)
In the last three decades there have been major changes in how surveying is practiced, and what surveyors have been trained and educated to do with the new expertise that technological advancements offer. Within surveying communities it is generally acknowledged that the changes in the profession have brought about an urgent need for change in educational programmes if they are to have relevance to contemporary practice.